Reclasser les victimes de la Première Guerre mondiale : Le cas de la loi du 30 janvier 1923 sur les emplois réservés en France (1923-1939) - Peggy Bette (Amnis)
In 1923, the French parliament members adopted a law reserving jobs in administrations and public establishments for war victims. The objective was to promote the social integration of thousands of war wounded, widows and orphans. Close to 150,000 of them benefited from reserved jobs between 1923 and 1939. Beforethat, they had to submit to a stringent selection system. The parliament members wanted it this way, because their main concern was to reconcile the war victims’ interests with the public service demands. At that time, no one raised the question of whether this system was compatible with the republican principles of equality. Their first wish was that the Nation fulfilled its duty towards the war victims.